Bioanalytical method development, validation and quantification of flupirtine maleate in rat plasma by liquid chromatography-tandem mass spectrometry - Kandasamy, Karthikeyan; Gowdra, Vasantharaju Surenahalli; Nammalvar, Hariprabhu; Govindarajan, Arul Kumaran Kottur S. (Arzneimittelforschung, 2011)
A simple, highly sensitive, precise and accurate high-performance liquid chromatographic (LCMSMS) method with mass detection was developed and validated for the rapid quantification of flupirtine (CAS 75507-68-5) in rat plasma samples. The chromatographic separation was achieved with a reverse phase column (4.6 × 50 mm, 5 µ m) and the mobile phase consisted of cyanomethane and 5 mM ammonium formate buffer pH 4.5 (70:30 v/v) as eluent, at a flow rate of 0.6 mL/min. Labetalol (CAS 36894-69-6) was used as an internal standard. The effluence was ionized by positive electro-spray ionization and measured by mass spectrometry. The retention times of flupirtine and labetalol were found to be 2.16 and 1.66 min respectively. The calibration curve was linear (r2 > or = 0.99) ranging from 0.98 to 1000 ng/ml and the lower limit of quantification was 0.98 ng/ mL. Inter-day and Intra-day precision were lower than 5% (CV) and accuracy ranged from 90 to 110% in terms of percent accuracy. Mean extraction recovery was found to be above 86.5%. The method was successfully applied for evaluation of the pharmacokinetic profile of flupirtine in male Sprague-Dawley rats and validated for excellent selectivity, accuracy, precision, recovery and stability.
Keywords: Electrospray ionization; Flupirtine; HPLC; Mass detection; Rat plasma; Validation